2011
DOI: 10.1177/1056789511427472
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Transition between Dense Metal and Damaged (Microporous) Metal Viscoplasticity

Abstract: This article presents a physically motivated approach, which has been developed in order to describe the transition of behavior between dense metal plasticity and microporous metal plasticity in the context of dynamic plasticity and adiabatic conditions. Considering that void germination requires a certain amount of plastic deformation, a 'primary' hole nucleation criterion as well as a statistical law governing the 'secondary' hole formation kinetics has been proposed. In a consistent way, the hole nucleation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…It must be noted that in the case where several bands are involved, one of them may be favored yielding the other to be inhibited and/or branching may occur between bands (see Fig.11b) leading to a tortuous band path -as observed experimentally, see e.g. Fig.9 of Longère et al (2012) and comments above relative to the shearcontrolled fracture of a plate specimen made of mild steel after interrupted tension loading. Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer 5 empty voids Fig.4c Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer 1 void + particle Fig.5a Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer 2 voids + particles Fig.5b Cell-to-cell strain localization within 4 parallel straight bands in the direction of the layer 8% 5 voids + particles Fig.5c Cell-to-cell strain localization within 4 parallel straight bands in the direction of the layer 1 empty void Fig.7a Cell-to-cell strain localization within 1 straight band in the direction of the layer 2 empty voids Fig.8a Void impingement within the cell and along the layer 5 empty voids Fig.9a Void impingement within the cell and along the layer 1 void + particle Fig.7b Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer 2 voids + particles Fig.8b Cell-to-cell strain localization within 1 straight band in the direction of the layer 25% 5 voids + particles Fig.9b Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer…”
Section: Void Concentration Evolutionmentioning
confidence: 71%
See 1 more Smart Citation
“…It must be noted that in the case where several bands are involved, one of them may be favored yielding the other to be inhibited and/or branching may occur between bands (see Fig.11b) leading to a tortuous band path -as observed experimentally, see e.g. Fig.9 of Longère et al (2012) and comments above relative to the shearcontrolled fracture of a plate specimen made of mild steel after interrupted tension loading. Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer 5 empty voids Fig.4c Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer 1 void + particle Fig.5a Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer 2 voids + particles Fig.5b Cell-to-cell strain localization within 4 parallel straight bands in the direction of the layer 8% 5 voids + particles Fig.5c Cell-to-cell strain localization within 4 parallel straight bands in the direction of the layer 1 empty void Fig.7a Cell-to-cell strain localization within 1 straight band in the direction of the layer 2 empty voids Fig.8a Void impingement within the cell and along the layer 5 empty voids Fig.9a Void impingement within the cell and along the layer 1 void + particle Fig.7b Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer 2 voids + particles Fig.8b Cell-to-cell strain localization within 1 straight band in the direction of the layer 25% 5 voids + particles Fig.9b Cell-to-cell strain localization within 2 parallel straight bands in the direction of the layer…”
Section: Void Concentration Evolutionmentioning
confidence: 71%
“…Moreover, in the micromechanics based analysis in Siruguet and Leblond (2004), it is shown that inclusions contained within voids act as a locking mechanism which may significantly modify the yield locus (notably when compared with the ones developed by Gurson (1977) and Gologanu et al (1997) for spherical and ellipsoidal cavities, respectively) and lead to void growth under zero stress triaxiality. In this line, a model was recently proposed based on a damage related softening mechanism acting as a kinematic stress drop causing a shift of the yield locus centre, see Longère et al (2012) and Longère and Dragon (2013). It must be noted that the aforementioned micromechanical studies all (more or less explicitly)…”
Section: Introductionmentioning
confidence: 99%
“…The damage at stake is coupled with plasticity and is supposed to occur as soon as a micro-void nucleation criterion is verified. The reader may refer to [1] for a detailed presentation of the guiding concepts of the model.…”
Section: Constitutive Relationsmentioning
confidence: 99%
“…The proposed modification is based on the hypothesis of a kinematic mean stress mechanism which governs a shift of the yield locus centre towards negative stress triaxiality values along the increasing damage. The modified GTN yield locus is given, according to [1], in the form…”
Section: Constitutive Relations For the Damaged Materialsmentioning
confidence: 99%
See 1 more Smart Citation